Features of designing of the grid connected photovoltaic station with a capacity of 10 kW - Yuldoshev I.A, Shoguchkarov S.Q, Jamolov T.R, Rustamova Sh.Sh (International Journal of Advanced Science and Technology, 2020)
Photovoltaic power station (PPS) operating function (without redundancy) with a nominal capacity of 10 kW connected to the low voltage electrical network established by "Zhejiang Chint Electrics Co Ltd" (PRC) under Tashkent conditions is defined. Analytical methods of calculation and design of PPS taking into account optimal distance between rows of photovoltaic batteries (PVB) are considered. The analysis of the results of the evaluation of the power generation of the PPS for the conditions of clear weather and clear cloudiness was carried out. According to the monitoring data for the winter period is 2211,5 kW*h.